Mobilisation of polish into german army from occupies polish territory in Second world war - Kaczmarek , Ryszard (Genocidas ir rezistencija, 2018)
At the outbreak of the Second World War, some of the local population of the territory annexed to the German Reich were granted partial or full German citizenship by Heinrich Himmler’s decree on the Deutsche Volksliste (German People’s List). At the same time, men of draft age, like other Reich citizens, became subject to military service. However, the first mass conscriptions to the German army in the annexed territory took place even earlier, in the spring of 1940. At the time, a rather strange term Deutsch-Polen (German Pole) was used in German internal correspondence to describe conscripts from the annexed part of Poland